Efficient chirp-assisted SRS in H2-filled hollow-core PCF for generation of ultrashort LP01 pulses at 1.8 μm - Loranger, Sebastien; Novoa, David; Russell, Philip St. John (Optics InfoBase Conference Papers, 2020)
Sub-40 fs pulses at 1.8 µm are generated by pumping H2-filled hollow-core PCF with 300 fs, 1.03 µm fiber laser pulses pre-chirped to a duration of 640 fs. Conversion efficiencies of 50% are obtained.
CRIS-Team Scopus Importer:2020-11-13